A guide to medicinal plants : an illustrated, scientific and medicinal approach - Koh, Hwee Ling (World Scientific Pub., 2009)
This book presents up-to-date information on a total of 75 native and non-native medicinal plants growing in Singapore. Comprehensive and useful information from the published literature - including plant descriptions and origins, traditional medicinal uses, phytoconstituents, pharmacological activities, adverse reactions, toxicities, and reported drug-herb interactions - is presented in an easy-to-read manner for easy and quick reference. There is no minimum level of knowledge required to read this book, and botanical and medical glossaries are also provided for readers' convenience. The book.